Biogas Compression in Gas Container and Application for Cooking - Panyaping, Klinpratoom; Jawana, Rotsukon; Ratbunthoeng, Khanidta; Pisitchaikon, Tidarat; Naprang, Thiramet (RMUTL Engineering Journal, 2021)
The purpose of this study was to investigate the quantity of biogas compression and storage, and the amount of heat at the pressure of 4 bars. Three experiments were conducted using gas containers of size 4, 6, and 15.8 kg. Each experiment was triplicated. The results showed that the 6 kg gas container had the highest quantity of biogas compression and storage at 12.07 L/min, which was equivalent to 64.21% of the 15.8 kg container. The higher and lower heating values of biogas compressed were 33,318.00 and 29,452.22 kJ/kg, respectively. The container size 15.8 kg had the quantity of biogas compression and storage of 7.35 L/min less than that of the container size 4 and 6 kg. The lower heating value of biogas was lower than that of LPG by 1.69 times. This finding indicates that the container size 6 kg was suitable for cooking in the field.